Understanding the combined effects of microcrystal growth and band gap reduction for Fe(1−x)TixF3 nanocomposites as cathode materials for lithium-ion batteries. (October 2015) - Bai, Ying; Zhou, Xingzhen; Jia, Zhe; Wu, Chuan; Yang, Liwei; Chen, Mizi; Zhao, Hui; Wu, Feng; Liu, Gao
Abstract: Whether FeF3 can take active part in electrochemical reaction is largely determined by its conductivity, which can be affected by the band gap and crystallite dimension. In this communication, the density of states (DOS) of FeF3 and Ti-doped FeF3 were calculated using a first principle density functional theory (DFT). Moreover, crystalline size was calculated according to Debye-Scherrer Equation. The results indicate that Ti-doping can reduce the band gap and impact the microcrystal growth of FeF3 at the same time. Both effects work synergistically on capacity loss and cycling stability; while impact antagonistically on charge transfer resistance ( R ct ), Li + diffusion coefficient (DLi + ) and specific capacity, leading to the excellent electrochemical performances of Fe(1− x ) Ti x F3 /C. The Fe0.99 Ti0.01 F3 /C nanocomposite achieves an initial capacity of 219.8 mA h/g and retains a discharge capacity of 173.6 mA h/g after 30 cycles at room temperature in the voltage range of 2.0–4.5 V. The hysteresis of discharge voltage plateau is significantly mitigated as well. In addition, the three-electron reaction of Fe0.99 Ti0.01 F3 /C during 1.0–4.5 V exhibits a high initial specific discharge capacity of 764.6 mA h/g. This study suggests that not only the band gap, but also the microcrystalline structure can be changed by Ti-doping, both of which have remarkable effects on the electrochemical properties, providing a new perspective on the effect of cation dopant. Highlights: First principle is used to calculate the density of states of Fe(1− x ) Ti x F3 . The effect of Ti-dopant on the microcrystal growth of Fe(1− x ) Ti x F3 is evaluated. A synergic-antergic mechanism is put forward to expound the combined effects. Fe0.99 Ti0.01 F3 /C nanocomposite shows a high capacity of 219.8 mA h/g in 2.0–4.5 V. The three-electron reaction of Fe(1− x ) Ti x F3 achieves 764 mA h/g in 1.0–4.5 V.